Artificial Intelligence Driven Dynamic Shuffling (DS) For Cloud Storage Employing Lightweight Techniques - Srisakthi, Dr. S.; Manju, Dr. G.; Roy, Dr. Tapabrata (Migration Letters, 2024)
From the dawn of cloud computing, the usage of cloud has been growing by leaps and bounds. One of the main usages of cloud is the storage service that it offers. In spite of its many creditable advantages, it also has some disadvantages like data security and data availability. These two are the main issues that a user faces from the time of its inception. Many models have been proposed to solve these issues. These models use cryptographic methods to secure the data. These methods solved the data security issue at the cost of extra storage space and increased time consumption both at the user and at the server side. These models have a limitation when it comes to resource-constrained devices. This paper ensures data security using lightweight techniques which brings in randomization by using the shuffling process. This paper proposes two models that perform shuffling in a dynamic manner. The Artificial Intelligence (AI) component decides the shuffling model that needs to be chosen. The Secure Dynamic Shuffling (SDS) model, executed by the user alone. Secret Shared Dynamic Shuffling (SSDS) model uses a secret sharing scheme, where both the user and the cloud provider share the secret. The proposed model gives a reduction of the storage space by 60%.